Les Déterminants de L’accroissement de L’horizon Spatial de Recherche D’emploi en Milieu Urbain Ivoirien - Coffie Francis José N’guessan (European Scientific Journal, ESJ, 2017)
The aim of this study is to obtain the determinants of spatial job search in urban Côte d'Ivoire. Due to the purpose of this study, we used the theory of Job search and a qualitative response model. The results indicated that the proximity to a local employment agency and social composition of the district play a significant role based on the decision of spatial job search. The findings of this study broadly confirmed the work of other authors in developed countries.